Effect of iron on crystallization and flow properties of coal ash slag: A combined computational-experimental study. (15th February 2023) - Zhang, Linmin; Song, Xudong; Wei, Juntao; Yang, Jianrong; Bai, Yonghui; Wang, Jiaofei; Yang, Huijun; Yu, Guangsuo
Highlights: Effect of iron on the crystallization and fluidity of ash slag was studied by MD simulation. The addition of iron resulted in low-temperature eutectic reaction and a reduced AFTs. Effect of iron on the crystal morphology was in-situ observed. Relationship among crystal morphology, polymerization degree and viscosity was discussed. Crystallization behavior was described by quantum chemistry and thermodynamics. Abstract: The crystallization and viscosity behavior of coal ash slag play a decisive role in the stable slagging of industrial gasifiers. However, the influence of iron on the crystallization and flow properties of slag is still poorly understood for its heterovalent component. Therefore, the influence of iron on the melting and crystallinity of slag was studied by preparing synthetic ashes with different iron contents, in this work. The results demonstrated that the ash fusion temperature (AFTs) could be significantly lowered with the increase of Fe content. This was because of the low-temperature eutectic reaction in slag caused by the increased iron content, which led to the transformation of the sub-liquid phase in slag from high-melting mullite to low-melting anorthite and spinel. At high temperature, iron was mainly presented in slag as Fe 2+ . At the same time, Fe 2+ as an alkaline component could terminate the interconnection between [SiO4 ] 4- and [AlO4 ] 5- tetrahedral by replacing Si 4+ and Al 3+ in slag. This consequence destroyed the slag network structure and lowered the polymerization degree. Slag with lower polymerization degree exhibited lower viscosity and stronger ionic transport capacity, which was favorable for crystal growth. Meanwhile, thermodynamic and quantum chemical calculations revealed that anorthite was a crystalline mineral during slag cooling.